The United Nations Security Council and War : The Evolution of Thought and Practice Since 1945 - Edited by Vanghan Lowe; Adam Roberts; Jennifer Welsh and Dominik Zaum (New York Oxford University Press 2008)
This text brings together leading scholars and practitioners to provide an analysis of the legal, historical, and political context in which the Security Council operates. They explore the different functions that the Council has acquired over the last 60 years, partly in response to the changing nature of war.
Include Appendix and Index
Keywords: United Nations. Security Council -- Security, International -- Intervention (International law)